Prevalência de asma e impacto da doença em escolares de uma região urbana de Porto Alegre - Roncada, Cristian (2014)
Background: Many developing countries have a high prevalence of asthma. However, the burden of disease has been scarcely reported from non-affluent populations. Aims: To assess the impact of the disease in Brazilian children with asthma from a large capital city. Methods: We selected inner-city children with asthma and healthy controls from public schools, between eight and 16 years of age, from a capital city of southern Brazil. The study was divided into three phases, with questionnaires (asthma prevalence, quality of life, knowledge and impact of disease) applied, with assessment of lung function, nutritional status and allergic sensitization. Results: From 2,500 children selected, with male gender of 1,211 (48.4%) and mean age of 11.42±2.32 years, 511 (20.4%) were diagnosed with asthma. The disease was not controlled in nearly half of the children with asthma, with a 7.5% of hospitalization rate in the last year. The majority of patients presented a history of dyspnea, exercise limitation or sleep disturbance because of asthma symptoms in the last 12 months, with high school absenteeism. Many patients required oral steroids in the previous year, and only 34% had a prescription of rescue medication, with 55% of passive smoking. Despite the free asthma medication access in Brazil since 2012, less than half of patients were using preventive treatment. Many parents assume that are not adherent to treatment and believe that rescue medication and exercise may be harmful. Conclusions: We have shown that the burden of asthma in children from southern Brazil is substantial, and this may reflect the scenario of many non-affluent populations worldwide. New international guidelines more focused in developing countries with pragmatic approaches should be a priority for discussion and implementation.